Ethical perspectives applied to the field of artificial intelligence - Terrones Rodríguez, Antonio Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2026)
The development of artificial intelligence (AI) will bring about significant transformations in various spheres of human action. The introduction of synthetic intellects into the human lifeblood raises a series of issues that must be addressed from the perspective of moral philosophy. In this regard, several ethical approaches are implicit in the postulates of certain AI theorists, and some are identified in this paper. This identification and subsequent categorization within various ethical currents aims to clarify the initiatives that have been undertaken within moral philosophy to analyze a technology characterized by ambivalence.
Keywords: artificial intelligence; moral philosophy; ethics; technological society